Macroeconomic Variables and Common Stock Returns in Nepalese Capital Market - Poudel, Shiva Raj (Journal of Business and Management, 2025)
Background: Capital Assets Pricing Model (CAPM) advocates the single predictive power of stock beta and argued that stock beta is only the factor which measure common stock returns to the extent on which the asset is corelated. However, Arbitrage Pricing Theory (APT) confirmed the multifactor effect on common stock returns. Therefore, the expected returns from the market can be the product of firm performance and the overall economy of the country.Objectives: The primary goal of the study is to examine how macroeconomic variables effect on the cross-section of expected stock returns in Nepali capital market.Methods: The study is based on data collected from 48 firms listed on the Nepal Stock Exchange (NEPSE), covering a 12-year period from 2010/11 to 2021/22, with total 576 observations. The dependent variables considered are capital gain yield, dividend yield, and total yield. Likewise, the explanatory variables are macro-economic variables such as GDP growth rate, consumer price index, money supply, Government Treasury bills and the lending rate. The analysis tools consist of descriptive statistics, correlation, and regression analysis.Results: The findings confirm that GDP growth, consumer price index, and money supply positively affect stock returns. In contrast, Treasury bills and lending rate have significant negative impact on common stock returns in Nepali stock market. The results obtained from the all-samples group were re-examined by stratified sample groups and confirmed the consistent results in almost all of the models applied.Conclusion: Macroeconomic variables are the key factors in predicting stock returns in Nepali capital market. Therefore, all the policy makers and investors practicing in Nepali capital market must analyze the economic condition of the country while taking important decisions.JEL Classification: E00, G10, G11, G12